Overall assessment of minimization tree logical structures - Ващук, Федір Григорович; Василенко, Юрій Андрійович; Повхан, Ігор Федорович (Eastern-European Journal of Enterprise Technologies, 2012)
The second work in a cycle of three articles devoted to a problem of an estimation of complexity of logic trees of classification. The question of an estimation of effect of minimization of logical trees of the fixed structure is investigated